Pre-operative maintenance of angiotensin-converting enzyme inhibitors is not associated with acute kidney injury in cardiac surgery patients with cardio-pulmonary bypass: a propensity-matched multicentric analysis - Pierre Guilleminot; Stefan Andrei; Maxime Nguyen; Maxime Nguyen; Osama Abou-Arab; Emmanuel Besnier; Belaid Bouhemad; Belaid Bouhemad; Pierre-Grégoire Guinot; Pierre-Grégoire Guinot; Collaborator study group; Jean-Baptiste Anciaux; et al. (Frontiers Media S.A., 2024)
Objective: We investigated the effects of the maintenance of angiotensin-converting enzyme inhibitors (ACE inhibitors) the day of the surgery on the incidence of postoperative acute kidney injury (AKI) and cardiac events in patients undergoing cardiac surgery.Methods: We performed a multicentric observational study with propensity matching on 1,072 patients treated with ACE inhibitors. We collected their baseline demographic data, comorbidities, and operative and postoperative outcomes. AKI was defined by KDIGO (Kidney Disease: Improving Global Outcome).Results: Maintenance of an ACE inhibitor was not associated with an increased risk of AKI (OR: 1.215 (CI95%:0.657-2.24), p = 0.843, 71 patients (25.1%) vs. 68 patients (24%)). Multivariate logistic regression and sensitive analysis did not demonstrate any association between ACE inhibitor maintenance and AKI, following cardiac surgery (OR: 1.03 (CI95%:0.81-1.3)). No statistically significant difference occurs in terms of incidence of cardiogenic shock (OR: 1.315 (CI95%:0.620-2.786)), stroke (OR: 3.313 (CI95%:0.356-27.523)), vasoplegia (OR: 0.741 (CI95%:0.419-1.319)), postoperative atrial fibrillation (OR: 1.710 (CI95%:0.936-3.122)), or mortality (OR: 2.989 (CI95%:0.343-26.034)). ICU and hospital length of stays did not differ (3 [2; 5] vs. 3 [2; 5] days, p = 0.963 and 9.5 [8; 12] vs. 10 [8; 14] days, p = 0.638).Conclusion: Our study revealed that maintenance of ACE inhibitors on the day of the surgery was not associated with increased postoperative AKI. ACE inhibitor maintenance was also not associated with an increased rate of postoperative major cardiovascular events (arterial hypotension, cardiogenic shock, vasopressors use, stroke and death).